Off-center-frequency analysis of a complete planar slotted-waveguide array consisting of subarrays. - Coetzee, J.C (IEEE Transactions on antennas and propagation)
An iterative procedure for calculating the off-center-frequency performance of a complete planar slotted-waveguide array, which consists of an arbitrary number of subarrays, is presented. The analysis includes the effects of the coupling slots from the main feed lines to the branch line guides, as well as the effects of RF manifolds, power splitters, or comparators used to distribute the power from the antenna input to the multiple subarray main lines. The procedure is applied to a large planar array for which dimensions have been obtained from an accurate metrology exercise. Good agreement between the predicted and measured performance of the array is demonstrated